Export Shocks and the Volatility of Returns to Schooling : Evidence from Twelve Latin American Economies - Lederman, Daniel (World Bank Group, Washington, DC, 2015)
This paper builds on previous studies to uncover evidence suggesting that cyclical fluctuations in returns to schooling are determined by fluctuations in foreign demand, which tend to be positively correlated with returns to schooling. The effect of export fluctuations (driven by changes in foreign demand) seems to be attenuated by labor market rigidities, such as constraints on employers to hire temporary workers on an hourly basis. This evidence suggests that countries that have flexible labor markets and experience volatility in their external demand might also experience volatility in returns to schooling. The paper discusses why this might be a concern for developing countries.